THE EFFORTS TO INCREASE STUDENTS' LEARNING OUTCOMES ON HEAT MATERIALS WITH COOPERATIVE LEARNING MODEL TYPE THINK PAIR SHARE (TPS) ASSISTED IN PHYSICS EDUCATION TECHNOLOGY (PhET) MEDIA AT CLASS X SEMESTER II SMA NEGERI BATANG KUIS T.P. 2019/2020 - Ritonga, Marlon (Jurnal Suluh Pendidikan, 2021)
This type of research is classroom action research (Classroom Action Research) with the aim of improving student learning outcomes on heat material with a cooperative learning model of Think Pair Share (TPS) type assisted by Physics Education Technology (PhET) learning media to improve student learning outcomes in class X semester II SMK Negeri 1 Dolok Merawan TP 2019/2020. The subjects of this study were all students of class X semester II SMA Negeri 1 Batang Kuis. The object of this research is the application of the Think Pair Share (TPS) cooperative learning model with the help of Physics Education Technology (PhET) media on vibration and wave material in class X SMA Negeri 1 Batang Kuis. The instruments used in this research are learning outcomes tests and student activity observation sheets that have been tested and declared valid. After the data is collected and analyzed, the results of data analysis are obtained: There is an increase in the average grade value from the initial test to the first cycle and from the first cycle to the second cycle by 35.76 to 56.53 and from 56.53 to 83.85. the percentage of completeness from the initial test to the first cycle is 26.92% and from the first cycle to the second cycle is 61.08%. This can be seen from the classical completeness of 0% to 26.92% and from 26.92% to 88%. From the results of the data analysis, it can be concluded that the Think Pair Share (TPS) Cooperative learning model assisted by the Physics Education Technology (PhET) learning media is able to improve learning outcomes in heat material for class X semester II students of SMA Negeri 1 Batang Kuis T.P. 2019/2020.